2012
DOI: 10.1007/s11738-012-0956-4
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and toxic effects of chromium and zinc in Iris pseudacorus L.

Abstract: The aim of the present study was to examine the ability of I. pseudacorus L., an ornamental macrophyte of great potential for phytoremediation, to tolerate and accumulate Cr and Zn. Plants were grown in nutritive solution with ZnCl 2 or CrCl 3 Á6H 2 O at 0, 10, 50, 100, and 200 lg ml -1 for 5 weeks; all survived and continued growing. The accumulation of Cr and Zn increased with increasing supply in all plant tissues, to reach 59.97 mg Cr and 25.64 mg Zn in roots. Leaves retained a remarkable amount of Zn (14.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 51 publications
3
25
0
Order By: Relevance
“…Significant reductions in plant height, as well as in shoot and root dry weight (varying from 3.3% to 54.5%), as compared with that of the controls, were found for Typha angustifolia plants in different Cr treatments [60]. Furthermore, according to Caldelas et al (2012) [19], not only growth inhibition happened (reached 65% dry weight) under Cr toxicity conditions, but also root/shoot partitioning increased by 80%. Under Cr stress conditions, it was found that root and shoot biomass of Genipa americana L. were significantly reduced [20].…”
Section: The Influence Of Heavy Metal Toxicity On Biomass Productionmentioning
confidence: 92%
See 2 more Smart Citations
“…Significant reductions in plant height, as well as in shoot and root dry weight (varying from 3.3% to 54.5%), as compared with that of the controls, were found for Typha angustifolia plants in different Cr treatments [60]. Furthermore, according to Caldelas et al (2012) [19], not only growth inhibition happened (reached 65% dry weight) under Cr toxicity conditions, but also root/shoot partitioning increased by 80%. Under Cr stress conditions, it was found that root and shoot biomass of Genipa americana L. were significantly reduced [20].…”
Section: The Influence Of Heavy Metal Toxicity On Biomass Productionmentioning
confidence: 92%
“…Under these conditions, plant growth and biomass are negatively affected [17][18][19][20]. According to Caldelas et al (2012) [19], not only growth inhibition happened, but also root to shoot dry matter partitioning (R/S) modified (increased 80%) at Cr toxic conditions in Iris pseudacorus L. plants. Some plant species, which may tolerate very high metal concentrations in their tissues, can be used as hyper-accumulators and are very suitable in reducing heavy metal concentrations in contaminated soils [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant aboveground (AG) and belowground (BG) parts were washed separately with tap water to remove particle deposition. The AG parts were not desorbed (no EDTA nor hard scrubbing) to preserve the fraction of metal adsorbed to cell walls, to enable comparison with what would happen after harvesting in CW [43]. Plant and pozzolan samples were dried at 80 °C over one week.…”
Section: Chemical Analysis In Water Substrate and Plantsmentioning
confidence: 99%
“…Sources of heavy metal contamination include anthropogenic activities, like use of pesticides, agriculture waste and industrial waste. Hexavalant chromium is considered the most toxic form because of its high solubility in water, which usually occurs amalgamated with oxygen as chromate or dichromate (Samantaray et al, 1998, Caldelas et al, 2012Hayat et al, 2012). Cr is known to induce production of elevated concentration of ROS resulted in macromolecule damage.…”
Section: Introductionmentioning
confidence: 99%